Системи управління технологічними процесами в умовах багатовекторності вимог - Жученко, А. І.; Ярощук, Л. Д.; Макаров, Т. В. (Видавництво Львівської політехніки, 2011)
The article investigates problem of developing control systems under the influence of sustainable development and other concepts. The authors propose their own scheme of control systems. The working methods of such system are considered as an example of soda production. The conclusion on the feasibility of its use is made.
Keywords: система управління; сталий розвиток; кальцинована сода; аналіз ієрархій; Сааті; SCADA